1987
DOI: 10.1128/jb.169.9.4313-4319.1987
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence and promoter mapping of the Escherichia coli Shiga-like toxin operon of bacteriophage H-19B

Abstract: We determined the nucleotide sequence of the Shiga-like toxin-1 (SLT-1) genes carried by the toxinconverting bacteriophage H-19B. Two open reading frames were identified; these were separated by 12 base pairs and encoded proteins of 315 (A subunit) and 89 (B subunit) amino acids. The predicted protein subunits had N-terminal hydrophobic signal sequences of 22 and 20 amino acids, respectively. The predicted amino acid sequence of the B subunit was identical to that of the B subunit of Shiga toxin. The A chain o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
119
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(123 citation statements)
references
References 46 publications
4
119
0
Order By: Relevance
“…The higher prevalence of infection among HUS-patients with VTEC producing only VT2 than infection with VTEC producing either only VT1 or a combination of VT1 and VT2, is consistent with other studies carried out in Western Europe and North-America [2,31]. However, Rowe and co-workers [32] recently found that 22 of the 26 0157. H7 VTEC isolates from Canadian HUSpatients produced both VT1 and VT2 rather than VT2 only.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The higher prevalence of infection among HUS-patients with VTEC producing only VT2 than infection with VTEC producing either only VT1 or a combination of VT1 and VT2, is consistent with other studies carried out in Western Europe and North-America [2,31]. However, Rowe and co-workers [32] recently found that 22 of the 26 0157. H7 VTEC isolates from Canadian HUSpatients produced both VT1 and VT2 rather than VT2 only.…”
Section: Discussionsupporting
confidence: 68%
“…Fifty-two human faecal VTEC isolates were studied, including 30 isolates from 19 children with D + HUS, nine isolates from family contacts (n = 9) of five of these HUS-patients, 11 2687-2706 * The position numbers are those in the published nucleotide sequences of VT1 [22], VT2 [23] and eae [24].…”
Section: Clinical Vtec Isolatesmentioning
confidence: 99%
“…This mechanism of action is shared by plant toxins such as ricin (Endo et al, 1987). Homology of the amino acid sequence of the processed A subunit of SLTs with ricin A chain has been noted by several workers (De Grandis et al, 1987;Calderwood et al, 1987;Weinstein et al, 1988) and recently, Hovde et al (1988) have demonstrated, with oligonucleotide-directed mutagenesis, that the glutamic acid residue at position 167 of SLTI is necessary for full enzymic activity of the toxin subunit. A number of common amino acids were noted from positions 165 to 206 of the processed SLTIIva A subunit and 175 to 215 of the ricin A chain (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Two open reading frames corresponding to the genes encoding the A and B subunits were located within this DNA fragment. Homology to the published DNA sequences and the predicted amino acid sequences of SLTs (Calderwood et al, 1987;De Grandis et al, 1987;Jackson et al, 1987a;Weinstein et al, 1988;Gyles et al, 1988) is summarized in Table 4. The DNA sequence of the B subunit gene had the closest relationship (98 %) to the B subunit region of sZtIIv while the A subunit gene had a similar level of homology to the A subunit genes of sZtIIv (70.6%) and sltII (6905%).…”
Section: Nucleotide Sequence Analysismentioning
confidence: 99%
“…The toxin family can be divided into two main groups, the first of which consists of Shiga toxin and VT-1. These are fully crossneutralizable and differ only in a single conservative amino acid substitution in the A subunit (6,7). The second group includes SLT-II, VT-2, and VTE which are partially crossneutralizable but are not neutralized at all by antiserum raised against Shiga toxin (3).…”
mentioning
confidence: 99%